Functional Imaging in Radiology: Assessing Metabolic and Molecular Changes in Disease Diagnosis - Anitha, V.; P, ashirwad; Kumar Ahirwar, Hement; Thomas, Sheffy Sabu; Sahil, Sk; V, Anoop (Journal of Neonatal Surgery, 2025)
Radiology has come to depend on functional imaging for the assessment of metabolic and molecular changes in disease, including cancer, neurological disorders, and inflammatory conditions. The purpose of this study is to evaluate the diagnostic effectiveness of three imaging modalities, Positron emission tomography (PET), Magnetic resonance imaging (MRI), and Single-Photon Emission computed tomography (SPECT), in identifying disease-specific metabolic and structural changes. A cohort of 150 participants was divided into cancer, neurological, and inflammatory disease groups. Mean standardized uptake values (SUV) were significantly higher in cancer patients (8.5 ± 2.3) than in neurological (4.2 ± 1.1) and inflammatory (3.8 ± 1.5) groups (p < 0.001). The mean apparent diffusion coefficient (ADC) in cancer patients (0.8 ± 0.2) was the lowest among all groups, which is consistent with restricted cellular movement (p < 0.001) indicative of malignancy. Regional cerebral blood flow (rCBF) analysis by SPECT showed higher perfusion in neurological patients (55.0 ± 15.0) than in cancer (40.0 ± 10.0) and inflammatory cases (45.0 ± 12.0), suggesting different perfusion requirements in different disease states (p < 0.01). Significant correlations between imaging parameters and clinical outcomes were demonstrated by correlation analysis, which highlights the value of multimodal imaging for personalized diagnosis. These findings confirm the complementary use of PET, MRI, and SPECT to image unique metabolic and structural markers to improve diagnostic precision and develop targeted treatment